Optimization of Interval Cost Multi-objective Transportation Problem in Uncertain Parameters: A Modified Least-Cost Method - Islam, Md Tariqul; Miah, Md Musa (Journal of Bangladesh Academy of Sciences, 2022)
The goal of this research is to focuses on multi-objective transportation problems, to reduce the cost of transporting a good from a variety of sources or origins to a range of destinations while adhering to a predetermined mathematical framework. By using interval values, the policy maker indicated the parameters of source and destination. In this work, a novel approach for finding initial basic feasible solutions (IBFS) that are extremely near to the best ones for a variety of transportation problems is presented. The proposed method can become a milestone in resolving the constraints to achieve the goal in solving transport problem. For the decision maker, regarding logistics and supply chains, it may be quite profitable. The prediction model is supported by an illustration drawn from mathematical view. All the LPPs are evaluated with the help of LINGO. Bangladesh Acad. Sci. 46(2); 155-164: December 2022